Performance comparison of a flexible circular microstrip patch antenna on various rubber-carbon compositions - Ruslan, Ahmad Alhadi; Yusoff, Siti Hajar; Mohamad, Sarah Yasmin; Ibrahim, Siti Noorjannah; Abdul Malek, Norun Farihah; Abd Rahman, Faridah (IEEE, 2023)
In this paper, a flexible circular microstrip antenna using rubber substrate is proposed to operate at 2.45 GHz within the ISM band for wearable applications. Several rubber materials with different carbon filler compositions have been selected as the substrate for the antenna. This includes natural rubber (no carbon filler), rubber with 20% carbon filler, rubber with 25% carbon filler and rubber with 50% carbon filler. The performances of these antennas are simulated and analyzed based on the S11, bandwidth and gain. The antennas are also compared to two other flexible substrates; PDMS and RO3003. Based on the simulation results, antenna with natural rubber exhibits the best gain, while antenna with rubber and 50% carbon filler exhibits the widest bandwidth.